2015
DOI: 10.1007/s13197-015-2063-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of doum (Hyphaene thebaica L.) flour addition on dough mixing properties, bread quality and antioxidant potential

Abstract: In this covenant of functional foods, the world seeks for new healthier food products with appropriate proportions of bioactive constituents such as fiber, mineral elements, phenols and flavonoids. The doum fruit has good nutritional and pharmaceutical properties; therefore, its incorporation in breads could be beneficial in improving human health. In the current study, partial substitution of wheat flour (WF) with doum fruit flour (DFF) at levels of 5 %, 10 %, 15 % and 20 % were carried out to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
4
16
1
Order By: Relevance
“…Also, the result due to fruit pigments and polyphenol components underwent oxidation reaction and sucrose was participated in caramelization and the Maillard browning during baking. These results were in harmony with those of Admassu et al, (2013) and Aboshora et al, (2016) they stated that the darkening of crust and crumb might have been attributed to high contents of total phenol of doum flour. Also, the Maillard reaction during baking might be due to high lysine content.…”
Section: Sensory Properties Of Fruit Cake Samplessupporting
confidence: 88%
“…Also, the result due to fruit pigments and polyphenol components underwent oxidation reaction and sucrose was participated in caramelization and the Maillard browning during baking. These results were in harmony with those of Admassu et al, (2013) and Aboshora et al, (2016) they stated that the darkening of crust and crumb might have been attributed to high contents of total phenol of doum flour. Also, the Maillard reaction during baking might be due to high lysine content.…”
Section: Sensory Properties Of Fruit Cake Samplessupporting
confidence: 88%
“…Previously, we have reported that Doum fruit possesses a high level of valuable component such as DF, carbohydrate, minerals, vitamins, flavonoids and polyphenol compounds (Aboshora et al 2014a, b). Moreover, the fruit has been used in bread production to improve its nutritional properties (Aboshora et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Segmentation of the tasters into two groups produced more precise models than those obtained using the global average. Equations (10) and (11) are the overall acceptability models for G1 and G2, respectively; these equations contain only the coefficients that result in the best statistical fit. For G1, the obtained model shows R 2 adjusted = 92.5%, P ANOVA = 0.0076 and a standard error of estimate of 0.19.…”
Section: Overall Acceptabilitymentioning
confidence: 99%
“…The partial substitution of wheat flour by yacon and maca flours could be an alternative to supply the demand of healthier products with sensorial characteristics comparable to traditional ones . The development of a new product is essentially an optimization problem, with the aim of searching for the ideal combination of ingredients .…”
Section: Introductionmentioning
confidence: 99%